Effect of Sodium Citrate and Urea as Additive on the Synthesis of Hydroxyapatite from Blood Cockle Shells: Kinetics and Adsorption Isotherms Study of Coomassie Brilliant Blue - Putri, Dhea Rahmanda; Jamarun, Novesar; Septiani, Upita; Sisca, Vivi (Indonesian Journal of Chemistry, 2025)
Hydroxyapatite (HAp) was synthesized from blood cockle shell waste by the sol-gel method, incorporating sodium citrate and urea as additives for Coomassie brilliant blue (CBB) adsorption. The synthesis included HAp without additives (HAp 1) and with 30 g/L of urea and varying sodium citrate concentrations of 0 (HAp 2), 0.1 (HAp 3), 0.2 (HAp 4), 0.3 (HAp 5), 0.4 (HAp 6), and 0.5 (HAp 7) g/L. HAp 4 showed the highest adsorption capacity at 96.60 mg/g. FTIR analysis of HAp 4 revealed adsorption bands for O−H and PO43− groups. XRD analysis indicated a crystal size of 24.55 nm with low crystallinity. SEM-EDS analysis showed a Ca/P ratio of 1.28, with an irregular shape due to agglomeration and an average particle size of 1.16 µm. SAA analysis found a surface area of 107.18 m2/g, a pore size of 12.55 nm, and a pore volume of 0.36 cm3/g. HAp 4 followed the Langmuir and pseudo-second-order isotherm models in CBB adsorption and demonstrated five-time reusability, proving it to be an effective adsorbent for CBB dyes.